Characterization of protein changes and development of flavor components induced by thermal modulation during the cooking of chicken meat. Issue 7 (5th April 2019) - Zhu, Chaozhi; Tian, Wei; Sun, Lingxia; Liu, Yanxia; Li, Miaoyun; Zhao, Gaiming
Abstract: With the development of new technology in the food industry, stewed chicken should now be prepared based on scientific processing parameters instead of traditional procedures. This study was designed to examine the effects of cooking temperature (75, 80, 85, 90, 95, and 100°C) and cooking time (10, 20, 30, 40, 50, 60, 90, and 120 min) on protein degradation, protein oxidation, and flavor formation in stewed chicken meat. Significantly greater nonprotein nitrogen and total free amino acid concentrations were observed when cooking at 80 and 90°C for 50 and 60 min. Cooking for 90–100 min resulted in a stable flavor profile according to e‐nose data. The results suggest that with a cooking temperature of 80–90°C and a cooking time of 50–60 min, protein degradation and protein oxidation are each maximized, indicating a critical point for increasing stewed chicken flavor formation. Practical applications: Heating of meat modifies its eating quality, including texture, color, and flavor. The rate and extent of these changes are dependent on the amount of heat that is transferred to the meat and on the heating rate. The ability to exert control over these variables will define to what extent the meat becomes more palatable to the consumer after cooking, with tenderness, juiciness, and flavor being the main factors influencing choice and acceptance of cooked meat. Therefore, a continuing aim of the meat industry is to discover improvements in processing that ensure and enhance these desirable sensory attributes while still yielding a product that is safe to consume.